Behavioral and cardiopulmonary effects of dexmedetomidine alone and in combination with butorphanol, methadone, morphine or tramadol in conscious sheep - Borges, Luisa Pb; Nishimura, Lilian T.; Carvalho, Leonardo L.; Cerejo, Sofia A.; Auckburally, Adam; Mattos-Junior, Ewaldo (Elsevier, 2016)
OBJECTIVE: To compare cardiopulmonary and sedative effects following administration of dexmedetomidine alone or with butorphanol, methadone, morphine or tramadol in healthy sheep. STUDY DESIGN: Randomized crossover study. ANIMALS: Six Santa Inês sheep, five females, one male, aged 12-28 months and weighing 40.1 ± 6.2 kg. METHODS: Sheep were assigned treatments of dexmedetomidine (0.005 mg kg(-1) ; D); D and butorphanol (0.15 mg kg(-1) ; DB); D and methadone (0.5 mg kg(-1) ; DM); D and morphine (0.5 mg kg(-1) ; DMO); or D and tramadol (5.0 mg kg(-1) ; DT). All drugs were administered intravenously with at least 7 days between each treatment. Rectal temperature, heart rate (HR), respiratory rate (fR ), invasive arterial pressure, blood gases and electrolytes were measured prior to administration of drugs (baseline, T0) and every 15 minutes following drug administration for 120 minutes (T15-T120). Sedation was scored by three observers blinded to treatment. RESULTS: HR decreased in all treatments and fR decreased in DM at T30 and DMO at T30 and T45. PaCO2 was increased in D, DB and DM compared with baseline, and PaO2 decreased in D at T15 and T45; in DB at T15 to T75; in DM at T15 to T60; in DMO at T15; and in DT at T15, T30 and T75. There was a decrease in temperature in D, DB and DM. An increased pH was measured in D at all time points and in DT at T30-T120. HCO3- and base excess were increased in all treatments compared with baseline. There were no statistical differences in sedation scores. CONCLUSIONS AND CLINICAL RELEVANCE: The combination of dexmedetomidine with butorphanol, methadone, morphine or tramadol resulted in similar changes in cardiopulmonary function and did not improve sedation when compared with dexmedetomidine alone.
Keywords: cardiopulmonary; opioids; ovine; α2-agonists